miR-3188 regulates nasopharyngeal carcinoma proliferation and chemosensitivity through a FOXO1-modulated positive feedback loop with mTOR–p-PI3K/AKT-c-JUN - Mengyang Zhao (Nature Portfolio, 2016)
Although miR-related mechanisms have been implicated in nasopharyngeal carcinoma (NPC), a precise role for miR-3188 has not been reported in this context. Here, Zhao et al. show that FOXO1-induced miR-3188 acts as a tumour suppressor in NPC by regulating the axis mTOR/PI3K/Akt/c-Jun.